Barney - Jinks, Catherine 1963-
Barney loves cat food. Barney loves greens. Barney loves bacon and biscuits and beans ... An extremely lovable book by two award-winning Australian children's book creators about an adorable family dog that will eat anything
Keywords: Dogs / Juvenile fiction; Food / Juvenile fiction; Australian fiction; Children's stories; Dogs; Food; Stories in rhyme; Picture books; Fiction; Juvenile works; Bilderbuch